2015
DOI: 10.1371/journal.pone.0144922
|View full text |Cite
|
Sign up to set email alerts
|

Envelope Proteins of White Spot Syndrome Virus (WSSV) Interact with Litopenaeus vannamei Peritrophin-Like Protein (LvPT)

Abstract: White spot syndrome virus (WSSV) is a major pathogen in shrimp cultures. The interactions between viral proteins and their receptors on the surface of cells in a frontier target tissue are crucial for triggering an infection. In this study, a yeast two-hybrid (Y2H) library was constructed using cDNA obtained from the stomach and gut of Litopenaeus vannamei, to ascertain the role of envelope proteins in WSSV infection. For this purpose, VP37 was used as the bait in the Y2H library screening. Forty positive clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…However, all of these genes were down regulated by ammonia stress in the shrimp ( S3 Table ). Xie et al [ 91 ] reported that the envelope proteins of WSSV interact with peritrophin protein in the stomach when WSSV infecting the L . vannamei , so the up-regulated expression of peritrophin by ammonia stress would increase the susceptibility to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these genes were down regulated by ammonia stress in the shrimp ( S3 Table ). Xie et al [ 91 ] reported that the envelope proteins of WSSV interact with peritrophin protein in the stomach when WSSV infecting the L . vannamei , so the up-regulated expression of peritrophin by ammonia stress would increase the susceptibility to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, we also observed a chitin metabolism-related gene, peritrophin-1 or A, among the immune-related genes expressed in the hepatopancreas of healthy shrimps. Peritrophin may interact with many proteins from the White Spot virus envelope and mediate its infection in Exopalaemon carinicauda [82] and L. vannamei [83,84] after virus injection. Studies have already reported that WSSV may have access to shrimp body through oral or waterborne routes [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Xie et al (2015), the P. vannamei peritrophin-like protein ( Lv PT) was found to interact with VP37, an envelope protein of the white spot syndrome virus. Further studies using the yeast two-hybrid (Y2H) library that was constructed using cDNA obtained from the stomach and gut of P. vannamei revealed that Lv PT could also interact with other WSSV envelope proteins such as VP32, VP38A, VP39B, and VP41A.…”
Section: Discussionmentioning
confidence: 99%
“…VP37, found on the outside of the virion WSSV membrane protein complex (Chang et al, 2010), played a major role in WSSV infection (Wu, Wang & Zhang, 2005). This envelope protein interacts with receptors or assisting proteins on the peritrophic membrane (PM), possibly peritrophin, that can enable the WSSV to break through the physical barrier of the PM (Xie et al, 2015). PM only allows particles smaller than 20 nm to pass through the membrane (Martin et al, 2006), wherein, the size and length of WSSV is 70–150 nm and 250–380 nm, respectively (Lu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%